CARBOTHERMIC REDUCTION OF MECHAICALLY ACTIVATED OF NiO-CARBON MIXTURE: NON-ISOTHERMAL KINETICS (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
The effect of mechanical activation on the carbothermic reduction of nickel oxide was investigated. Mixtures of nickel oxide and activated carbon (99% carbon) were milled for different times in a planetary ball mill. The unmilled mixture and milled samples were subjected to thermogravimetric analysis (TGA) under an argon atmosphere and their solid products of the reduction reaction were studied using XRD experiments. TGA showed that the reduction of NiO started at ~800℃ and ~720℃ in un-milled and one-hour milled samples respectively whilst after 25 h milling it decreased to about 430℃. The kinetics parameters of carbothermic reduction were determined using non-isothermal method (Coats-Redfern Method) for un-milled and milled samples. The activation energy was determined to be about 224.8 kJ mol-1for un-milled mixture whilst it was decreased to about 161 kJ mol-1 in 25 -h milled sample. The decrease in the particle size/crystallite size of the as-milled samples resulted in a significant drop in the reaction temperature